Inseminação artificial em caprinos com sêmen resfriado. - Amanda Pimenta Siqueira (2006)
The objective of this study was to evaluate the fertilizing capacity of goat semen cooled in egg yolk diluent at 5oC, by 12 (TI) or 24 hours (TII). Sixty two Toggenburg female goats (11 nuliparous, 28 lactating, 14 dry and 2 with unknown condition), were uniformly distributed in two groups, as previously mentionated. Semen was collected from two sexually mature Toggenburg goat bucks. After being collected, the semen was diluted in Tris-frutose-egg yolk 2.5% and then envased in 0.25ml plastic straws, with 150 million mobile spermatozoa, cooled at 5oC for 12 or 24 hours. The females received two doses of 22.5µg of prostaglandine F2, 10 days apart. After the first and second injections, the estrus was monitored 3 times a day (6:00, 12:00 and 18:00h), with a buck teaser. Just one insemination was used, by the cervix fixation method. The pregnancy was detected using a trans-rectal ultra-sound (5MHz probe), on 21, 30 and 60 days after artificial insemination. The average motility and strength, after 12 or 24 hours of cooled semen at 5oC was 66.14 ± 0.11% and 62.50 ± 0.05%, and 3.46 ± 0.61 and 3.27 ± 0.50, respectively. The percentage of animals that showed estrus after the first and second injection of PGF2 was 85.48% and 88.71%, respectively. The average intervals from first and second PGF2 injection to estrus was 41.04 ± 20.32 and 45.67 ± 9.28h, and the estrus duration for both injections was 40.02 ± 15.96 and 32.24 ± 12.09h, in this order. The interval from the PGF2 injection to beginning of the estrus was longer (P<0.05), whereas the estrus duration was shorter (P<0.05) in the estrus induced after the second PGF2 injection. The semen storage length (12 or 24 hours) did not affect (P>0.05) the conception rate obtained. The total conception rate was 49.09%. In the same way, the age difference did not affect (P>0.05) the pregnancy rate in inseminated goats. On the other hand, the mucous observed in the insemination time has influenced (P<0.05) the fertility of inseminated goats, with the striated aspect associated to higher fertility.